Role of Micronutrients in Tissue Repair and Physiotherapeutic Rehabilitation Outcomes (International Journal of Food and Nutritional Sciences, 2021)
Tissue repair is a complex biological process involving cellular regeneration, inflammation control, and remodeling which are the key determinants of successful rehabilitation following injury or surgery. While physiotherapeutic outcomes provides mechanical and functional stimuli for recovery, nutritional factors, particularly micronutrients such as vitamin D, zinc, and magnesium, play crucial biochemical roles in tissue healing, muscle recovery, and neuromuscular coordination. Vitamin D is essential to maintain strong and healthy bones by supporting mineralization, growth, and repair of the skeletal system. Magnesium contributes to essential biochemical pathways, acting as a cofactor in protein making, collagen formation, and tissue repair. Zinc aids in immune function, DNA synthesis, protein and collagen formation, cell growth, and the restoration of damaged tissues. Emerging evidence indicates that deficiencies in these micronutrients can delay healing, impair muscle strength, and compromise physiotherapy outcomes. Minerals are required by the body for many important functions. If athletes don’t get enough, their performance can suffer. This article reviews the physiological functions of vitamin D, zinc, and magnesium in tissue repair and their synergistic influence on rehabilitation success. Understanding these interactions can guide integrated therapeutic strategies combining physiotherapy with targeted micronutrient optimization.